The impact of attitude toward COVID-19 vaccine on intention to receive influenza vaccination: a multi-group comparison based on the influence of presumed influence model and spillover effects - Zhang, Yun; Yi, Hongfa (Frontiers in Public Health, 2024)
Introduction Influenza vaccination is one of the most important strategies for preventing influenza. However, the influenza vaccination rate in China remains low. During the COVID-19 pandemic, people held different attitudes toward the COVID-19 vaccine. In the post-pandemic era, do the varying attitudes toward the COVID-19 vaccine affect the intention to receive influenza vaccination? Methods Based on the influence of presumed influence (IPI) model and spillover effects, this study employed structural equation modeling for multi-group comparison to analyze questionnaires from 613 participants, using instruments such as the Perceived Media Influence on Others Scale (PMIO), the Susceptibility to Influenza Scale (SI), and the Attitude toward Influenza Vaccine Scale (AIV). Results The key findings are as follows: (1) Information exposure to the influenza vaccine significantly influences perceived media influence on others. (2) Perceived media influence on others does not directly impact the intention to receive influenza vaccination but rather affects it through attitude toward the influenza vaccine. (3) Moreover, multi-group analyses revealed differences in the IPI model among audiences with different attitudes toward the COVID-19 vaccine. These differences demonstrated that prior attitudes toward the COVID-19 vaccine can influence attitudes toward similar influenza vaccines, thus demonstrating the existence of spillover effects. Conclusion Attitude toward the COVID-19 vaccine can influence the intention to receive the influenza vaccination. Those with a negative attitude toward the COVID-19 vaccine are significantly influenced by susceptibility to influenza. Perceived media influence affects the intention to receive the influenza vaccination among those with a positive attitude toward the COVID-19 vaccine.